Radiotherapy plus concomitant temozolomide in primary gliosarcoma - Adeberg, Sebastian; Bernhardt, Denise; Harrabi, Semi B.; Diehl, Christian; Kölsche, Christian; Rieken, Stefan; Unterberg, Andreas; Deimling, Andreas von; Debus, Jürgen (Journal of neuro-oncology, 2016)
Clinical guidelines for gliosarcoma (GSM) are poorly defined and GSM patients are usually treated in accordance with existing guidelines for glioblastoma (GBM), with maximal surgical resection followed by chemoradiation with temozolomide (TMZ). However, it is not clear yet if GSM patients profit from TMZ therapy and if O6-methylguanine-DNA-methyltransferase (MGMT) promoter methylation is crucial. We retrospectively evaluated 37 patients with histologically proven, primary GSM who had received radiation therapy since the temozolomide era (post-2005). Twenty-five patients (67.6 %) received combined chemoradiation with temozolomide, and 12 cases (32.4 %) received radiation therapy alone. Molecular markers were determined retrospectively. Survival and correlations were calculated using log-rank, univariate, and multivariate Cox proportional hazards-ratio analyses. All cases were isocitrate dehydrogenase 1 (IDH1) wildtype, MGMT promoter methylation could be observed in 33.3 % of the assessable cases (10/30) and TERT promoter mutation was seen in a high frequency of 86.7 % (26/30). The influence of TMZ therapy on overall survival (OS) was significantly improved compared with cases in which radiation therapy alone was performed (13.9 vs. 9.9 months; p = 0.045), independently of MGMT promoter methylation. The positive effect of TMZ on OS was confirmed in this study’s multivariate analyses (p = 0.04), after adjusting our results for potential confounders. In conclusion, this study demonstrates that concomitant TMZ together with radiation therapy increases GSM-patient survival independent of MGMT promoter methylation. Thus, GSM can be treated in accordance to GBM guidelines. MGMT promoter methylation was infrequent and TERT promoter mutation common without influencing the survival rates. The mechanisms of TMZ effects in GSM are still not fully understood and merit further clinical and molecular-genetic and -biological evaluation.